STRATEGI PEMASARAN AGROWISATA PERKEBUNAN KOPI SEKITAR GUNUNG GUMITIR KABUPATEN JEMBER - Ufi Inani Sangadah; Sukidin Sukidin (Economic Education, University of Jember, 2016)
Tourism development should pay attention to the preservation of environmental quality, because in the tourism industry, the environment that actually sold. One alternative tourism development that can maintain the quality of the environment to maintain its sustainability is agrotourism. Agro tourism is a tourist attraction that utilize agricultural land for the attraction. One of agrotourism in the district of Jember is Agro Tourism Gumitir Mountain Coffee Plantation gives a new sensation that distinctiveness owned natural mountain. Based on the existing problems, the objectives to be achieved in this research is to describe the marketing strategy agro coffee estates around Mount gumitir Jember. This research is descriptive research with a qualitative approach. Location research using purposive area, while to determine the study subjects using purposive sampling method. Data collection methods used consisted of interviews, observation, and documents. Analysis of the data used is data reduction, data presentation, and conclusion. The results showed that the Agro Plantation Coffee Mount Gumitir use various marketing strategies in marketing their products. Marketing strategy undertaken by a team of marketing agro first is mapping the area to be used as a marketing venue. Then connected with marketing as more private uses a strategic one on one, door to door, and a SWOT analysis. In addition to using these strategies, agro tourism also use STP strategy (segmentation, targeting, positioning) to enter the desired market segment. Team marketing of agro expected over optimize 4P marketing strategies. Optimization 4P marketing strategies can be more focused on the promotion so that consumers who visit not only domestic consumers but also foreign.